PENGARUH KEGIATAN MELIPAT KERTAS (ORIGAMI) TERHADAP KETERAMPILAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK AL-HISA DI KECAMATAN TENAYAN RAYA PEKANBARU - Norhayati, Norhayati; Chairulsyah, Daviq; Hukmi S, Hukmi S (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of the activities of paper folding (origami) on fine motor skills of children aged 4-5 years in kindergarten Al-Hisa District of Tenayan Raya Pekanbaru. The sample in this study were 20 children consisting of 9 boys and 11 girls. Data collection techniques were used that observation. The data analysis technique used in this study is t-test analysis. The results were obtained from the results of hypothesis testing roduct moment correlation (r) with r = 0.50 and a value table for n = 20 and a 5% error, then the tables r = 0.444. Provisions when the count r is smaller than r table, then Ho is accepted and Ha rejected. Found r count larger than r table (0.50> 0.444), so that Ha is accepted. This means that there are significant activities of paper folding (origami) on fine motor skills of children aged 4-5 years. To find out the hypothesis is accepted or rejected based on the data SPSS version 16.0 for Windows, it can be seen from the comparison of t arithmetic with t table. From the calculation of the t-test found the results t -21.666 where the value (-) is not used (Sugiyono: 2008) so that the t (21.666). This means that t = 21.666 bigger than t table = 1.734 at 5% error level. Thus Ho rejected and Ha accepted. From this study it can be concluded that the activity of paper folding (origami) significantly affect the fine motor skills of children aged 4-5 years in kindergarten Al-Hisa District of Tenayan Raya Pekanbaru.Key words: Paper folding (origami), fine motor,experiment